2020
DOI: 10.3389/fendo.2020.00085
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Female Reproduction: An Expanding Universe

Abstract: For more than a half century the hormone melatonin has been associated with vertebrate reproduction, particularly in the context of seasonal breeding. This association is due in large measure to the fact that melatonin secretion from the pineal gland into the peripheral circulation is a nocturnal event whose duration is reflective of night length, which of course becomes progressively longer during winter months and correspondingly shorter during the summer months. The nocturnal plasma melatonin signal is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 111 publications
(101 reference statements)
0
40
0
2
Order By: Relevance
“…Hormones. The hormone melatonin regulates behaviour and metabolic and immune functions and has antioxidant and ROS-scavenger properties, crucial for reproductive health [ 147 ]. A PCOS patient’s melatonin ameliorates mitochondrial functions by increasing the levels of SIRT1 and sirtuin protein and regulating mitochondrial functions via deacylation.…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%
“…Hormones. The hormone melatonin regulates behaviour and metabolic and immune functions and has antioxidant and ROS-scavenger properties, crucial for reproductive health [ 147 ]. A PCOS patient’s melatonin ameliorates mitochondrial functions by increasing the levels of SIRT1 and sirtuin protein and regulating mitochondrial functions via deacylation.…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%
“…Furthermore, the neuroprotective ( Alghamdi, 2018 ) and cardioprotective ( Lochner et al, 2018 ) abilities of melatonin have previously been demonstrated. Melatonin has beneficial properties in female reproduction ( Olcese, 2020 ) and male fertility ( Kratz and Piwowar, 2017 ). Moreover, melatonin plays essential roles in controlling metabolic diseases ( Cardinali and Hardeland, 2017 ; Karamitri and Jockers, 2019 ), ocular diseases ( Scuderi et al, 2019 ), and rheumatologic diseases ( Jahanban-Esfahlan et al, 2018 ).…”
Section: Melatonin and Its Potentialsmentioning
confidence: 99%
“…Human studies indicated that during the pre-pubertal phase, serum melatonin levels peaked and decreased progressively, and in a significant way, were proportional to sexual maturation, which led to the onset of pubertal changes [ 33 ]. Similarly, high plasma melatonin levels are associated with prepubertal and delayed pubertal conditions, whereas a low level of melatonin is associated with the post-pubertal state or CPP [ 34 ].…”
Section: Discussionmentioning
confidence: 99%